Deceptive Utterances Captured in Rian Johnson's Knives Out - Miftakhul Khoiroh (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This research aims to analyze the deceptive utterances in a movie entitled Knives Out (2019). Different from previous research, this research does not only focus on one character, but also the other characters who are potentially being deceptive. By doing analysis based on theory of types of deception, this qualitative research analyzed the video of the movie along with the script to solve the research problems regarding how the utterances in the movie can be categorized as deceptive utterances. Moreover, this research also used the theory of deception motive to investigate the relationship between motive and the type of deception employed by the characters. The results show that the movie contains 23 deceptive utterances, and the motive influences the characters in determining what type of deception strategy they should use. This research contributes to the existing knowledge of deception by pointing out that each character uses deception in two different kinds of purposes: deception to achieve their goal, and deception to save them in unfavorable circumstances. Keywords: deceptive utterances, motives, types of deception strategy, Knives Out Abstrak: Penelitian ini bertujuan untuk menganalisis ujaran-ujaran menipu dalam film berjudul “Knives Out” (2019). Berbeda dengan penelitian sebelumnya, penelitian ini tidak hanya fokus pada satu karakter saja, tetapi juga pada karakter lain yang juga berpotensi menipu. Dengan melakukan analisis berdasarkan teori jenis-jenis penipuan, penelitian kualitatif ini menganalisis video film beserta naskahnya untuk memecahkan masalah penelitian tentang bagaimana ujaran-ujaran dalam film dapat dikategorikan sebagai ujaran-ujaran menipu. Selain itu, penelitian ini juga menggunakan teori motif penipuan untuk menyelidiki hubungan antara motif dan jenis penipuan yang digunakan oleh karakter. Hasil penelitian menunjukkan bahwa film tersebut mengandung 23 ujaran penipuan dan motif mempengaruhi karakter dalam menentukan jenis penipuan apa yang harus mereka terapkan. Secara umum, motif dibagi menjadi dua: penipuan untuk mencapai tujuan mereka, dan penipuan untuk menyelamatkan mereka dalam keadaan yang tidak menguntungkan. Kata kunci: ujaran menipu; motif; jenis strategi penipuan;  “Knives Out”